Islamic Republic of Mauritania : 2012 Article IV Consultation and Fourth Review Under the Three-Year Extended Credit Facility Arrangement, and Requests for Waivers of Nonobservance and Modification of Performance Criteria-Staff Report and Supplement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Islamic Republic of Mauritania. (IMF Staff Country Reports; Country Report ;, 2012)
The 2012 Article IV Consultation and Fourth Review under the three-year Extended Credit Facility (ECF) Arrangement discusses the macroeconomic conditions of the Islamic Republic of Mauritania. Mauritania's economy has performed well in 2011, despite significant challenges. Economic activity is likely to pick up and inflation to remain low. However, Mauritania faces important short- and medium-term policy challenges, notably in the social area, where progress in reducing poverty has been slow and unemployment is still high. The performance under the ECF-supported program has remained strong.